The populist threat to liberal democracy - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
Populism is no longer considered a disease of the developing world. In recent decades it has spread throughout Europe and North America, while maintaining its grip in its historical stronghold, Latin America. It now represents the biggest threat to the survival of liberal democracy. Unlike communism, which attacked liberal democracy frontally and sometimes violently, populism works from within, neutralizing institutional and cultural antibodies. If not stopped, it naturally evolves towards authoritarianism. With different strategies and at different speeds, communism and populism achieve the same goal: the destruction of liberal democracy.
Keywords: 330; Populismus; Autoritarismus; Demokratie; Welt